Skrining Gangguan Postur Tubuh dan Edukasi Postur Tubuh yang Ideal pada Siswa SD Inpres Bung Tahun 2024 - Hamisah, Hamisah; Nawir, Dian Amaliah; Sabriyati, Wa Ode Nur Isnah; Handayani, Komang Trisna; Nusantara, Hebat Maha Putera (Universitas Baiturrahim, 2025)
The number of students' learning activities is proportional to the number of items they bring to school using bags. The results of previous research at SD Inpres Bung, Makassar City showed that the degree of risk of scoliosis with a moderate level of asymmetry was 64 (44.4%) respondents and the degree of risk of scoliosis with a normal level of asymmetry was 63 (43.7%) of respondents. This activity is carried out in two stages, namely: (a) preparation stage, and (b) implementation stage. From all of this activity, it is known that the highest ATR degree score is 10 students and the average ATR degree score is two degrees, namely 33 students (21.15%). There was an increase in knowledge of 93.58%, both about ideal posture and posture disorders. With the assistance of the service team, an overview of the risk of scoliosis has been obtained and students have understood the correct body posture and detected the body posture of students who are experiencing problems.